Artificial Intelligence Applications in Rare Skin Diseases - WANG Yukun; LIU Jie (罕见病研究, 2023)
In clinical practice, early diagnosis, accurate assessment and effective management of rare skin diseases are difficult. The Big Data gives rise to the exponential growth of biomedical data, including medical images, multi-omics information and electronic health records. Artificial intelligence (AI), particularly machine learning, has its advantage in processing complex and abundant information. Researches have applied AI in the field of rare skin diseases. In this paper, we briefly describe, discuss, and foresee the research on AI based image data, multi-omics data & text data and AI in assisting rare skin disease drug development, in order to improve the awareness of dermatologist understanding of this field and actively promote the development of AI usage on rare skin diseases.